PENGARUH MEDIA QUIZIZZ TERHADAP KETERAMPILAN MENULIS TEKS DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Elvina Vatima Nija; Chusnul chotimah; Muhammad Farid Nurul Anwar (Universitas Tribhuwana Tunggadewi, 2026)
Elementary school pupils' poor writing skills are attributed, in part, to their persistent dependence on conventional teaching methods and their disregard for interactive technology. The goal of this research was to ascertain how primary school students' text writing skills in learning Indonesian are impacted by the usage of Quizizz media. Data was gathered via pretests, posttests, questionnaires, observations, and documentation. Students in the experimental class had higher final grades than those in the control class, according to the data, at a significance level of 0.000 less than 0.05. Furthermore, the experimental class's gain in learning outcomes (N-Gain) fell into the medium group, while the control class fell into the low category. This suggests that using Quizizz considerably and more effectively enhanced students' writing skills as compared to more conventional teaching strategies.